2010
DOI: 10.1177/8756479310366471
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Contribute to Wrist-Hand-Finger Discomfort in Diagnostic Medical Sonographers and Vascular Technologists

Abstract: A cross-sectional representative sample of 1722 sonographers and vascular technologists was analyzed using quantitative/qualitative methods to reveal that 60% are experiencing wrist-hand-finger discomfort, believed to be from work-related repetitive injury. The years of scanning accumulated by the participants was chosen as a variable to determine the relationship to the range of discomforts reported. A strong statistical correlation was noted between years of experience and the side of discomfort as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 17 publications
4
38
0
Order By: Relevance
“…8,25 Obesity is on the increase 24 and in 2011, the Royal College of Obstetricians and Gynaecologists 26 suggested that approximately 1 in 5 pregnant women were obese, with a BMI of 30. It is important to ensure that limited pressure is placed on the transducer, as pushing can increase transducer grip, which may lead to injury.…”
Section: Other Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,25 Obesity is on the increase 24 and in 2011, the Royal College of Obstetricians and Gynaecologists 26 suggested that approximately 1 in 5 pregnant women were obese, with a BMI of 30. It is important to ensure that limited pressure is placed on the transducer, as pushing can increase transducer grip, which may lead to injury.…”
Section: Other Factorsmentioning
confidence: 99%
“…It is important to ensure that limited pressure is placed on the transducer, as pushing can increase transducer grip, which may lead to injury. 25 Techniques that can be used to reduce the risk of muscle injury when scanning obese patients include optimising the equipment, using lower frequency and a range of factors such as harmonics, compound imaging or trying transvaginal scanning, where appropriate. 24 Lifting the panniculus (subcutaneous tissue in the lower abdomen) or scanning from above or to the side of the panniculus can help, 24 as can decubitus scanning or the use of the Sims position, where the patient is almost prone and scanning is from the flank, to reduce the depth of tissue for the sound to penetrate.…”
Section: Other Factorsmentioning
confidence: 99%
“…Some of these symptoms may cause a loss of muscle strength, making it difficult to hold a transducer. [4][5][6]11 Eye strain, although not a symptom of WRMSD itself, can lead to blurred vision and poor posture. As this is a cumulative disorder, seemingly minor symptoms can progress over time to more serious, even debilitating, symptoms.…”
Section: Injury Symptoms and The Impact Of Injurymentioning
confidence: 99%
“…11 Gripping the ultrasound transducer contributes to this injury and can lead to "trigger finger," which occurs when the tendon sheath becomes edematous and traps the finger tendon in a locked position. 4,6,[12][13][14] Another form of tendonitis is De Quervain syndrome, which occurs at the base of the thumb and is also associated with gripping the ultrasound transducer department's bottom line, worker morale, and the quality of patient care.…”
Section: Injury Symptoms and The Impact Of Injurymentioning
confidence: 99%
“…an echocardiogram). A patient examination may take 15 to 45 minutes (Evans et al, 2010), depending on the amount of images, measurement and annotation required, as well as challenges posed by the patient’s anatomy. Most exams are performed in outpatient clinics or hospital patient rooms; some are performed in other locations in the hospital.…”
Section: Introductionmentioning
confidence: 99%